Association between HDL-cholesterol subfractions and the risk of major adverse cardiac and cerebrovascular events in patients with acute myocardial infarction: a single-center retrospective observational study - Geng, Yu; Deng, Xingfei; Xue, Yajun; Wang, Bin; Liu, Qing; Lv, Tingting; Lv, Changhua; Wang, Yifei; Zhang, Ping (Frontiers in Nutrition, 2026)
BackgroundThis study aimed to evaluate the association between high-density lipoprotein (HDL) subfractions and long-term major adverse cardiac and cerebrovascular events (MACCEs) in patients with acute myocardial infarction (AMI).MethodA total of 1,240 AMI patients admitted to Beijing Tsinghua Changgung Hospital between 2017 and 2023 were included. HDL subfractions, including HDL-2b and HDL-3, were quantified using microfluidic chip electrophoresis. Patients were stratified into tertiles according to HDL-3 levels. The primary endpoint was the occurrence of MACCEs. Kaplan–Meier analysis, Cox proportional hazards models, restricted cubic spline (RCS), and mediation analyses were performed to evaluate the associations between HDL subfractions and MACCEs.ResultDuring a median follow-up of 52.4 months, 132 MACCEs (10.7%) occurred. Patients in the highest HDL-3 tertile had a lower MACCEs incidence than those in the lowest tertile (6.7% vs. 16.4%, p < 0.001). Higher HDL-3 levels were associated with improved event-free survival (HR = 0.58, 95% CI: 0.37–0.91) and demonstrated discriminative ability for MACCE risk (AUC = 0.62; 95% CI: 0.57–0.67), whereas HDL-C and HDL-2b were not significant. RCS analysis revealed a linear inverse association between HDL-3 and MACCEs (p for non-linearity = 0.356). The Gensini score partially mediated this relationship, accounting for 11.8% of the total effect.ConclusionLower HDL-3 levels were independently associated with a higher long-term risk of MACCEs in AMI patients. HDL-3 may represent a potential biomarker for residual cardiovascular risk stratification and a potential therapeutic target for improving post-infarction outcomes.